Pengaruh Brand Image Terhadap Keputusan Pembelian Produk Chicken Nugget Champ di Kabupaten Kudus - Lam'aa, Nisrina Fauzia; Roessali, Wiludjeng; Setiyawan, Hery (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
This research aims to analyze the influence of brand image on purchasing decisions for the Champ brand chicken nugget product in Kudus Regency. The research was conducted at Bitingan Market and ADA Supermarket in September-October 2023. The survey method was used in this study, with samples taken using accidental sampling and involving 100 respondents responsible for household food shopping. The data obtained were analyzed using multiple logistic regression to determine the influence of corporate image, consumer image, and product image on purchasing decisions. The results of the study show that brand image has a significant effect on the purchasing decision for Champ chicken nuggets, with the most significant variable being product image (X3) on the purchasing decision in Kudus Regency. The variables of corporate image (X1) and consumer image (X2) do not significantly affect purchasing decisions for Champ chicken nuggets in Kudus Regency. This study highlights the importance of enhancing product image to attract consumer interest in purchasing decisions.